2011
DOI: 10.1007/s00012-011-0142-3
|View full text |Cite
|
Sign up to set email alerts
|

Axiomatizability of positive algebras of binary relations

Abstract: We consider all positive fragments of Tarski's representable relation algebras and determine whether the equational and quasiequational theories of these fragments are finitely axiomatizable in first-order logic. We also look at extending the signature with reflexive, transitive closure and the residuals of composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 21 publications
0
46
0
Order By: Relevance
“…We note that non-finite axiomatisability of representability of algebras with signature τ where {·, ∧, ∨} ⊆ τ ⊆ {·, ∧, ∨,˘, e, 0, T} was shown by Andréka [1]; see also Andréka and Mikulás [2].…”
Section: A Embeds Into a [Finite] Group Gmentioning
confidence: 82%
See 1 more Smart Citation
“…We note that non-finite axiomatisability of representability of algebras with signature τ where {·, ∧, ∨} ⊆ τ ⊆ {·, ∧, ∨,˘, e, 0, T} was shown by Andréka [1]; see also Andréka and Mikulás [2].…”
Section: A Embeds Into a [Finite] Group Gmentioning
confidence: 82%
“…We have already observed that both versions of (3) are known to be undecidable, and so too are the items in (1) and (2). The goal of this paper is to introduce equivalent statements regarding decidability of representability of signatures weaker than that of a Boolean monoid.…”
Section: A Embeds Into a [Finite] Group Gmentioning
confidence: 99%
“…Usually, these operations can be expressed in terms of operations of Tarski's algebras of relations. Algebras with such operations are called reducts of Tarski's algebras of relations [23,1,2,8].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that RRA is a variety [Ta55], but it cannot be defined by any finite set of first-order formulas [Mo64], hence the equational theory is not finitely based. There has been some interest in identifying subsignatures τ of the full relation algebra signature such that the corresponding representation class Q(τ ) (defined formally below) is defined by a finite set of axioms, or where the set of equations valid over Q(τ ) follows from a finite set of equations, see [Sc91,Mi04,AM10] for surveys. It is known that Q(τ ) is a finitely axiomatizable quasivariety if τ ⊆ {0, 1, +, • , −, 1 , }.…”
Section: Introductionmentioning
confidence: 99%